Analisis Efektivitas Perusahaan dengan Model Du Pont System - Bagja Pasca Ramadhan; Acep Samsudin; Dicky Jhoansyah (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the Du Pont System model in analyzing the effectiveness of the company's operations in generating profits at PT. Gajah Tunggal Tbk. This study uses quantitative descriptive analysis techniques that are used to describe in measuring the effectiveness of the company after carrying out calculations with the figures that have been included in the components or formulas contained in the Du Pont System model that is the Profitability Ratio consisting of Net Profit Margins (Net Profit Margin) and Return on Investment (Return On Investment), then Activity Ratio which consists of Total Asset Turnover. Conclusion, the effectiveness of the company for five years is considered not good seeing the decline that occurred in several aspects that could affect the final value of the Du Pont System. Keywords: Company Effectiveness, Du Pont System